"Food Meant Everything to Me, Now Food Is Something I Eat:" Managing Emotions, Perceptions, and Awareness of Food and Eating After Bariatric Surgery. (29th May 2020) - Ujayli, Deema; Quadrini, Isabella; Lynch, Amanda
Abstract: Objectives: This study explores the cognitive changes made by bariatric surgery patients, focusing on their perceptions of food, the role of food in their lives, and what drives them to make their food choices. Comparing pre-surgery and post-surgery experiences provides insight into the dietary changes that occur as a result of bariatric surgery. Methods: Thirty bariatric surgery patients (24 women, 6 men) completed dietary and behavior questionnaires and participated in semi-structured interviews pre-surgery, and at 6 and 12 months post-surgery. Interview questions covered participants' weight histories, dietary behaviors, perceptions of food, and surgery experiences. Verbatim interview transcripts were coded and analyzed using a constructivist, grounded theory approach. Emergent themes were compared across time points and within each time point to identify patterns of change and common experiences. Results: Relationship to food emerged as a multidimensional phenomenon that included emotional eating, beliefs about the function of food and nutrients, and positive or negative perceptions of food. The majority of participants reported emotional eating before surgery. Post-surgery, half of the participants no longer struggled with emotional eating. The four most common emotions that led to eating were stress, depression, boredom, and happiness. The primary theme relating to the function of food was a shift from "living to eat" to "eating to live." With this shift came an increased awareness and appreciation of food, nutrients, and health. Participants' perceptions of food and eating were either positive, encompassing feelings of enjoyment, happiness, and/or appreciation, or negative, expressed by feelings of frustration, anxiety, and fear. Perceptions of food were influenced by pre-surgery relationship to food, dieting history, and current contexts. Conclusions: Bariatric surgery patients have strong and multifaceted connections to food before and after surgery. Relationship to food impacts food choices as well as the mental effort and energy put forth in making dietary decisions. Understanding these relationships may be an important aspect of post-surgical counseling, particularly for patients experiencing less than ideal weight loss outcomes. Funding Sources: Oakland University and William Beaumont Hospital.